Telerehabilitation in Chronic Obstructive Pulmonary Disease (COPD) Management: Exploring Experiences and Effectiveness - Promsarn, Simaporn; Rattanasaengloet, Kanokwan (Journal of Health Science and Medical Research, 2024)
Telerehabilitation has emerged as a promising approach to address the challenges posed by chronic obstructive pulmonary disease (COPD) management. This article provides a comprehensive review of telerehabilitation’s characteristics,components, efficacy, patient experiences, and the implications for COPD patients. Telerehabilitation involves the use of telecommunication technologies to remotely deliver rehabilitation services, including exercise training, education, and monitoring, to individuals with COPD. It addresses barriers such as geographical distance and limited access to specialized facilities, making rehabilitation accessible from home. Telerehabilitation encompasses various approaches, including telemonitoring, teleconsultation, and tele-education. Several studies have indicated positive outcomes in exercise capacity, dyspnea, and quality of life when comparing telerehabilitation interventions to standard care or traditional rehabilitation programs. However, challenges related to technology access, digital literacy, and privacy need to be addressed for equitable implementation. Interdisciplinary collaboration among healthcare professionals is essential for the successful delivery of telerehabilitation. Future research should focus on refining the interventions, standardizing the protocols, and evaluating the long-term maintenance effects. By integrating patient-centered approaches and leveraging advancements in digital technologies, telerehabilitation can revolutionize COPD management strategies, enhancing patient outcomes in the modern healthcare landscape.